An approach to the challenges of e-learning in times of COVID-19 - Carballo-Barcos, Miriam (2023)
The challenges of virtual learning in times of COVID-19 were analyzed at the Faculty of Education of Secondary Education of the “Félix Varela Morales” Pedagogical Headquarters, of the “Marta Abreu” de Las Villas Central University, located in the city of Santa Clara, Villa Clara Cuba between the years 2020-2021. The Materialist Dialectic was used as a general method, and the methods of the historical-logical, analytical-synthetic, and inductive-deductive theoretical level. Bibliographic sources were reviewed including journal articles, books, research reports, and documents that deal with the subject mainly between the years 2020-2021. Among the main results, the need to work in the direction of threegreat challenges stands out: the efficient use of technological resources available in Cuban universities, the preparation of teachers and students for virtual learning, and the didactic organization of each one of the subjects. It is concluded that an approach to these three challenges of virtual learning in times of pandemic is required.